Monitoring the levels of phi and tau group GST genes in wheat cultivars under osmotic stress - Gallé, Ágnes (Acta Biologica Szegediensis, 2008)
GST isoenzymes represent a large and variable group of antioxidative enzymes, with several different activities and sequence patterns. The GST activities of the isohydric drought-tolerant Triticum aestivum L. cv. Kobomugi and the anisohydric cv. Öthalom were measured after one week of 400 mOsm polyethylene glycol (PEG) treatment. The GST activities were much higher in the roots than in the shoots and were induced by PEG especially in the roots. The aim of our work was to sort out the osmotic stress related wheat GST genes. The changes in enzyme activities and expression of several GST-coding sequences were in good correlation. Both cultivars responded to osmotic stress. Higher induction, especially in phi class GSTs was detectable in the isohydric Kobomugi cultivar. Elevations were measured in the ranscript amounts of six different GST genes.